Mean platelet volume vs. optical platelet volume measurement: which is a better indicator for neonatal sepsis? - Yang Hao; Bao Jiqian; Guo Siqi; He Jiajing; Ye Lei; Zhang Yingjun; Dai Qingkai; Zhang Ge (Journal of Laboratory Medicine)
To evaluate the accuracy of mean platelet volume (MPV) testing in the neonatal population and assess the applicability of the optical platelet volume measurement method on Sysmex XN9000 in this demographic.